2011
DOI: 10.4028/www.scientific.net/amr.228-229.580
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Synthesis and Optical Properties-Controlling Studies of CdO Nanoparticles

Abstract: CdO nanoparticles with different sizes were synthesized by a simple thermal decomposition reaction of precursor obtained by room-temperature solid-state grinding reaction between Cd(CH3COO)22H2O and NaOH in the presence of PEG400. Composition, structure and morphology of the products were analyzed and characterized by X-ray diffraction technology, Transmission electron microscopy and Fourier infrared spectra. The formation of CdO nanoparticles is thought that the nucleation rate of the reactive system is far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The literature reported energy value of 3.73‐3.81 eV for In 2 O 3 and 2.2‐2.5 eV (direct band gap), 1.98 eV (indirect band gap) for CdO agrees well with the measured data for In 2 O 3 and CdO obtained in this work. However, the absorption at lower energy levels observed for CdO in the present case, that is 768 nm (1.61 eV) against the reported value of 720 nm (1.72 eV), could be attributed to the defects (deep traps and surface states) present in the CdO particle . The UV‐Vis and photoluminescence data for β ‐PbO (figure 6c) show absorptions between 492 nm (2.52 eV, inset PL) and at 247 nm (5.02 eV, UV‐Vis curve).…”
Section: Resultssupporting
confidence: 88%
“…The literature reported energy value of 3.73‐3.81 eV for In 2 O 3 and 2.2‐2.5 eV (direct band gap), 1.98 eV (indirect band gap) for CdO agrees well with the measured data for In 2 O 3 and CdO obtained in this work. However, the absorption at lower energy levels observed for CdO in the present case, that is 768 nm (1.61 eV) against the reported value of 720 nm (1.72 eV), could be attributed to the defects (deep traps and surface states) present in the CdO particle . The UV‐Vis and photoluminescence data for β ‐PbO (figure 6c) show absorptions between 492 nm (2.52 eV, inset PL) and at 247 nm (5.02 eV, UV‐Vis curve).…”
Section: Resultssupporting
confidence: 88%
“…It has been shown that the PL spectra for the CdO reveal a multi-line structure which is identified in terms of free exciton and exciton complexes with neutral donors and deep centers. [30,31] Interestingly, the changes observed in the properties of our CdO nanocrystalline material from their counter bulk material are due to the fact that crystallite size becomes comparable to Bohr's excitonic radius (r B ) given by the expression; (1) where ε is the permittivity of CdO, and are the effective mass of electron and hole in CdO respectively. The determined particle sizes are comparable to the Bohr excitonic radius and supporting the quantum confinement effect.…”
Section: Resultsmentioning
confidence: 96%
“…These recombination mechanisms compete with the exciton-related luminescence and seem to depend on the stiochiometry and the preparation conditions of the CdO rather than on their microstructure. [30,31] A small kick on the left side of the blue emission is also found for the sample prepared at 180°C which is unknown to us and it may be due to some impurities present in the product as indicated in the Raman, FT-IR and XRD studies. It has been shown that the PL spectra for the CdO reveal a multi-line structure which is identified in terms of free exciton and exciton complexes with neutral donors and deep centers.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The nanomaterials prepared using the solid-state reaction are characterized by their low cost, dispensing with washing and separation steps, low energy consumption, low harmful emissions, mass production, high stability, ease of preparation and transportation. Regarding these advantages, many researchers have worked on developing solid-state reaction methods to prepare various nanomaterials such as Cu and Cu 3 Au, [17] Ag, [18] VO 2 , [19] CdO, [20] Ag@plypyrrole, [21] Au@Ag core@shell, [22] ZnO, [23] and Ag-Cu 2 O/graphene oxide. [24] However, these solid-state preparation routes include the use of hazardous reducing agents such as sodium borohydride, hydrazine hydrate, ethylene glycol, etc., and the use of expensive reagents.…”
Section: Introductionmentioning
confidence: 99%